Synthesis, characterisation and biological activities of N-phenyl-ethan-1-one-2,4-dimethyl-1,3-butadiene-1,4-thiazin derivatives - Nabaz Abdulmajeed Mohammad Salih (Tikrit Journal of Pure Science, 2023)
A facile synthesis of some new 1, 2- thiazine derivatives by the Claisen-Schmidt reaction-induced aldolic condensation of enolizable aromatic ketones with substituted benzaldehydes, and then they were treated with urea and thiourea to obtain the corresponding pyrimidine derivatives. IR, 1H and 13C-NMR spectroscopy were used to analyze all produced substances.  The synthesized compounds (5, 9-11 and 14-15) were screened for their biological activity against two species of bacteria and fungi according to the gram stain, and all compounds indicated growth inhibition against Escherichia coli, Staphylococcus aureus, and fungi respectively with different inhibition zones starting from 11 to 26 mm. In all cases, the used two doses were (10 mg/ 1 ml in DMSO) and (20 mg/ 1ml DMSO).